INVESTIGASI PENGGUNAAN MEREK HANDPHONE DI PROVINSI RIAU (Pendekatan Rantai Markov) - Herispon, Herispon (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
This study tries to trace, analyze and show the market share of mobile phone brand users, especially in Riau Province. The data collection technique was carried out using an online survey method, covering the entire province of Riau. Respondents who participated filled out online questionnaires that were distributed and sent back as many as 490 respondents. The data analysis method used was the Markov Chain approach. Research shows that nationally in 2021 and 2022 the Samsung and Apple mobile phone brands have increased market share, in Riau Province the market share has actually decreased. Meanwhile, the use of OPPO, VIVO, Iphone and Realmi mobile phones in Riau Province has an increasing market share. In conclusion, the price factor and attractive features are the choices of the respondents studied.